Microbiota-based markers predictive of development of Clostridioides difficile infection - Matilda Berkell; Mohamed Mysara; Basil Britto Xavier; Cornelis H. van Werkhoven; Pieter Monsieurs; Christine Lammens; Annie Ducher; Maria J. G. T. Vehreschild; Herman Goossens; Jean de Gunzburg; Marc J. M. Bonten; Surbhi Malhotra-Kumar; et al. (Nature Communications, 2021)
Clostridioides difficile infection (CDI) is the most common cause of antibiotic-associated diarrhoea (AAD); however, markers predictive of CDI or AAD development are as yet lacking. Here, to identify markers predictive of CDI, the authors profile the intestinal microbiota of 945 hospitalised patients from 34 hospitals in 6 different European countries and show distinct microbiota enriched in Enterococcus and depleted of Ruminococcus, Blautia, Prevotella and Bifidobacterium compared to non-CDI patients.